How does happiness relate to economic behaviour?: a review of the literature - Lane, Tom (Elsevier, 2017)
This article reviews research on the relationship between happiness (subjective wellbeing) and economic behaviour. I describe how experimental and non-experimental methods have been used, across the social sciences, to investigate how happiness drives, and is driven by, particular behavioural tendencies. I consider interpersonal behaviour (selfishness, trust and reciprocity) and individual behaviour (risk and time preferences). Regarding interpersonal behaviour, a general conclusion is that happiness results from pro-social behaviour. Happiness negatively correlates with selfishness and positively correlates with trust; in both cases there is stronger evidence that the behaviour is a cause of happiness than a consequence of it. Individuals also gain happiness from inflicting costly punishment on those who have harmed them, although being happy reduces the degree to which people are willing to dole out such punishment in the first place. Regarding individual behaviour, the relationship between happiness and risk preferences remains unclear despite a large body of research on the topic, while there is evidence that happiness affects time preferences by reducing impatience. In all cases, I draw distinctions between the long- and short- term relationships between happiness and behaviour.